Penerapan Metode Statistical Process Control (SPC) untuk Pengendalian Kualitas Produk Kopi Cibulao - Diki Ripandi; Silvera Marsya Aleida; Hany Handayani; Renhard Cornelis Wiyanto; Oppy Rahmi Fazri; Rizda Dwiyanti; Fany Apriliani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study applies the Statistical Process Control (SPC) method for quality control of Cibulao coffee production in Cisarua District, Bogor Regency. Although the coffee production in this area cannot yet meet market demand, Cibulao coffee is considered a specialty product with a unique taste. By using SPC, this research aims to monitor and control product quality, identify causes of non-conformance, and improve the quality of the coffee sustainably, ensuring it meets market standards and enhances the competitiveness of Cibulao coffee.